2018
DOI: 10.1590/1414-431x20187151
|View full text |Cite
|
Sign up to set email alerts
|

Icariin reduces human colon carcinoma cell growth and metastasis by enhancing p53 activities

Abstract: Icariin has been reported to possess high anticancer activity. Colon carcinoma is one of the leading causes of cancer-related mortality worldwide. Here, the anticancer activity of icariin against HCT116 colon carcinoma cells and the possible underlying mechanism were studied. The trypan blue staining assay, wound healing assay, clonogenic assay, CCK-8 assay, and Annexin V-FITC/PI double staining method were carried out to determine the changes of HCT116 cell growth and migration. mRNA and protein expressions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 27 publications
(27 reference statements)
1
17
0
Order By: Relevance
“…For example, Ren et al showed that icariin inhibited osteosarcoma cell proliferation [26]. Similarly, icariin exerted suppressive effects on colon cancer cells [27], thyroid cancer cells [28] and ovarian cancer cells [29]. The induction of S-phase arrest and apoptosis were observed in medulloblastoma cells after treatment with icariin [30].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ren et al showed that icariin inhibited osteosarcoma cell proliferation [26]. Similarly, icariin exerted suppressive effects on colon cancer cells [27], thyroid cancer cells [28] and ovarian cancer cells [29]. The induction of S-phase arrest and apoptosis were observed in medulloblastoma cells after treatment with icariin [30].…”
Section: Introductionmentioning
confidence: 99%
“…10 In addition, Tian et al reported that ICA reduced human colon carcinoma cell growth and metastasis activity. 13 In this study, we primarily identified that ICA inhibited the proliferation and invasion of SCC-9 and SCC-15 cells and suppressed the tumor growth in vivo. Our present study firstly revealed that ICA could impede the growth and metastasis of OSCC.…”
Section: Discussionmentioning
confidence: 92%
“…As previous researches reported, ICA has a variety of pharmacological benefits including anti-osteoporosis, 7 anti-cardiovascular, 8 antitumor 9,10 and organ protection. 11,12 Interestingly, ICA has been proved to suppress ovarian cancer, 9 thyroid cancer, 10 colon cancer 13 and osteosarcoma 14 via different signals. However, the anti-OSCC role of ICA has not been discussed yet.…”
Section: Introductionmentioning
confidence: 99%
“…P53 is an important tumor suppressor, and its overexpression leads to arrest of the cell cycle and promotion of the apoptosis of cancer cells. Thus, we could speculate that the overexpression of p53 might be involved in the anti-cancer potential of ICA [ 13 ], where cubosomal delivery has a potential role in improving efficacy by improving the cellular availability of ICA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that ICA induces apoptosis and suppresses autophagy via the overexpression of autophagy-related p53 in breast cancer cells [ 11 ] and that it inhibits the invasion and migration of gastric cancer cells by the vasodilator-stimulated phosphoprotein via the Rac1 pathway [ 12 ]. Metastasis and growth of colon cancer was reported to be inhibited by enhancing p53 activity through the regulation of caspase and the imbalance of BCL-2/Bax [ 13 ]. In spite of the well-established anticancer potential of ICA, its therapeutic application is limited because of its poor solubility in the aqueous environment, which results in poor bioavailability (~0.1%) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%